USING ICT TOOLS TO DEVELOP STUDENTS’ CRITICAL THINKING SKILLS - Шарипхазина, Ж.К. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The issues of developing critical thinking skills, replenishing and enriching the vocabulary of students are among the most pressing problems of modern pedagogical science and practice. In the conditions of scientific progress, more and more new words come into use, many of which are difficult and incomprehensible. Therefore, the primary task of the teacher is to work on enriching and clarifying the vocabulary of students: the more words a person speaks, the more accurately communication between people is realized, both orally and in writing.
Keywords: critical thinking; vocabulary; ICT tools